Dysregulation of prostaglandins, leukotrienes and lipoxin A4 in bronchiectasis. Issue 10 (17th November 2021) - Bedi, Pallavi; Ziegler, Kerstin; Whitfield, Phil D; Davidson, Donald; Rossi, Adriano Giorgio; Hill, Adam T
Abstract : Introduction: Bronchiectasis is characterised by excessive neutrophilic inflammation. Lipid mediators such as prostaglandins and leukotrienes have crucial roles in the inflammatory response. Further characterisation of these lipids and understanding the interplay of anti-inflammatory and proinflammatory lipid mediators could lead to the development of novel anti-inflammatory therapies for bronchiectasis. Aim: The aim of our study was to characterise the lipids obtained from serum and airways in patients with bronchiectasis in the stable state. Methods: Six healthy volunteers, 10 patients with mild bronchiectasis, 15 with moderate bronchiectasis and 9 with severe bronchiectasis were recruited. All participants had 60 mL of blood taken and underwent a bronchoscopy while in the stable state. Lipidomics was done on serum and bronchoalveolar lavage fluid (BALF). Results: In the stable state, in serum there were significantly higher levels of prostaglandin E2 (PGE2 ), 15-hydroxyeicosatetranoic acid (15-HETE) and leukotriene B4 (LTB4 ) in patients with moderate–severe disease compared with healthy volunteers. There was a significantly lower level of lipoxin A4 (LXA4 ) in severe bronchiectasis. In BALF, there were significantly higher levels of PGE2, 5-HETE, 15-HETE, 9-hydroxyoctadecadienoic acid and LTB4 in moderate–severe patients compared with healthy volunteers. In the stable state, there was a negative correlation of PGE2 and LTB4 with % predicted forced expiratory volume in 1 s and a positive correlation with antibiotic courses. LXA4 improved blood and airway neutrophil phagocytosis and bacterial killing in patients with bronchiectasis. Additionally LXA4 reduced neutrophil activation and degranulation. Conclusion: There is a dysregulation of lipid mediators in bronchiectasis with excess proinflammatory lipids. LXA4 improves the function of reprogrammed neutrophils. The therapeutic efficacy of LXA4 in bronchiectasis warrants further studies.